2008
DOI: 10.1086/522896
|View full text |Cite
|
Sign up to set email alerts
|

Economic Status, Informal Exchange, and Sexual Risk in Kisumu, Kenya

Abstract: Many observers believe that wealthy men play a disproportionate role in the continuing spread of HIV/AIDS infection in sub-Saharan Africa through their involvement in informal exchange relationships, where money and gifts (referred to as "transfers") are given to a range of nonmarital sexual partners. In this case, wealthier men are riskier sexual partners because they can afford to give larger transfers, which have been found to be negatively associated with condom use. Alternatively, wealthier men might have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…For example, the only available measure in the DHS of condom use-''condom use by respondent during last sexual intercourse''-is a restricted measure of proclivity compared to a measure of consistent condom use, and past research suggest that the former is not as related to HIV prevalence and engagement in protective behavior as the later [49]. Nevertheless, a number of other studies employing the last-intercourse measure found significant effects on reduction of HIV infection, and a significant positive association between condom-at-last-sex and consistent condom use [50][51][52][53][54][55][56][57][58].…”
Section: Limitationsmentioning
confidence: 99%
“…For example, the only available measure in the DHS of condom use-''condom use by respondent during last sexual intercourse''-is a restricted measure of proclivity compared to a measure of consistent condom use, and past research suggest that the former is not as related to HIV prevalence and engagement in protective behavior as the later [49]. Nevertheless, a number of other studies employing the last-intercourse measure found significant effects on reduction of HIV infection, and a significant positive association between condom-at-last-sex and consistent condom use [50][51][52][53][54][55][56][57][58].…”
Section: Limitationsmentioning
confidence: 99%
“…First, mathematical models highlight the potential role of age-disparate relationships in propagating the epidemic across generations [5]. Second, relationships in which the man is considerably older than the woman are believed to be more likely than similarly-aged partnerships to exhibit power imbalances, due to older men having more economic resources and social standing [6–9], providing more opportunity for their partners to pressure the women into riskier sexual behaviors [10,11]. Such risky behaviors in age disparate relationships are particularly troubling since rising HIV prevalence with age [1] implies that older male partners are more likely to be HIV infected than men the women’s own age.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect there is a growing body of work on men, boys and masculinities in southern Acknowledging the pressures on men to take multiple partners in proving sexual prowess, such practices have received increasing attention in the larger HIV/AIDS literature (Do & Meekers 2009;Luke 2005). While research findings are ambiguous in this respect, with some showing that multiple partner practices do not necessarily increase vulnerability to HIV (Luke 2008), the pressure on men to be sexually active, coupled with other forms of risk taking, such as resistance to condom use, as discussed above, and the use of alcohol and other substances, are of concern within the context of the high rates of HIV infection in southern Africa.…”
Section: Introductionmentioning
confidence: 99%